Argonaute2 modulates megakaryocyte development and sex-specific control of platelet protein expression and reactivity - Sophia Lazar; Jeremy G.T. Wurtzel; Shayan Askari; Matthew Cooper; Xuefei Zhao; Peisong Ma; Lawrence E. Goldfinger (Scientific Reports)
Abstract Platelets are enriched in miRNAs and harbor Ago2 as the principal RNA silencing Argonaute. However, roles in thrombopoiesis and platelet function remain poorly understood. We generated megakaryocyte/platelet-specific Ago2-deleted (Ago2 KO) mice and assessed proteomic and functional effects. We predicted platelet hyperreactivity with Ago2 deletion due to large-scale upregulated protein expression. Platelet counts were normal. Mean volumes were increased, associated with larger, though fewer megakaryocytes. Ago2-deleted platelets from male mice showed hyperreactivity to thromboxane but not to other agonists compared to controls, whereas Ago2-deleted platelets from female mice showed normal reactivity. Ago2 KO mice displayed normal hemostasis and clot dynamics. Proteomes of Ago2-deleted and wild type platelets were mostly similar. However, Ago1 - undetectable in wild type platelets - was upregulated in Ago2-deleted platelets in both males and females, confirmed by immunoblotting. Female Ago2-deleted platelets selectively showed downregulation of a protein cohort established in breast cancer cells to be transcriptionally regulated by estrogen receptor-beta coupled to Ago2, whereas male Ago2-deleted platelets did not. Thus, Ago2 is important for platelet development and function, putatively partially rescued by upregulation of Ago1. Platelet reactivity controlled by Ago2 reflects sex-specific regulation of gene expression potentially at both transcriptional and translational levels in megakaryocytes and platelets.